2013
DOI: 10.1021/es401968c
|View full text |Cite
|
Sign up to set email alerts
|

Seeming Steady-State Uphill Diffusion of 22Na+ in Compacted Montmorillonite

Abstract: Whereas the transport of solutes in nonreactive porous media can mostly be described by diffusion driven by the concentration gradients in the external bulk water phase, the situation for dense clays and clay rocks has been less clear for a long time. The presence of fixed negative surface charges complicates the application of Fick's laws in the case of ionic species. Here we report the seeming uphill diffusion of a (22)Na(+) tracer in compacted sodium montmorillonite, that is, transport directed from a low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 26 publications
1
61
0
Order By: Relevance
“…The comparably large values may be explained by the so-called surface diffusion of sorbed cations (including cations in the diffuse layer and in interlayers), which leads to an additional driving force for diffusion besides the pore-water gradient (e.g. Glaus et al 2013). From a normalisation of a large number of published tracer cation diffusion data, Gimmi and Kosakowski (2011) (Lauber et al 2000).…”
Section: Cation Diffusion Coefficientsmentioning
confidence: 99%
“…The comparably large values may be explained by the so-called surface diffusion of sorbed cations (including cations in the diffuse layer and in interlayers), which leads to an additional driving force for diffusion besides the pore-water gradient (e.g. Glaus et al 2013). From a normalisation of a large number of published tracer cation diffusion data, Gimmi and Kosakowski (2011) (Lauber et al 2000).…”
Section: Cation Diffusion Coefficientsmentioning
confidence: 99%
“…The comparably large values may be explained by the so-called surface diffusion of sorbed cations (including cations in the diffuse layer and in interlayers), which leads to an additional driving force for diffusion besides the pore-water gradient (e.g. Glaus et al 2013). From a normalisation of a large number of published tracer cation diffusion data, Gimmi and Kosakowski (2011) could show that normalised effective cation diffusion coefficients D erw generally increase with a normalised sorption capacity of the cation.…”
Section: Cation Diffusion Coefficientsmentioning
confidence: 99%
“…The validity of this basic approach has been recently demonstrated in experiments in which the concentration gradients of the cation exchanging species were adjusted in a deliberate manner by establishing significant concentration differences between the two background electrolyte solutions (Glaus et al, 2013). In these experiments tracer diffusion was in the direction of the reservoir containing the higher concentration in the aqueous phase but with less tracer bound to the clay phase.…”
Section: Introductionmentioning
confidence: 99%
“…Specific investigations (Glaus et al, 2010(Glaus et al, , 2013 and an exhaustive compilation of literature data (Gimmi and Kosakowski, 2011) for diffusion in a broad variety of clay media and soils indicated that surface diffusion in argillaceous media may largely be described by the concentration effects mentioned above. Other model approaches are, however, also applicable and it may be difficult to design experiments, by which a discrimination between the various model approaches is enabled (Ochs et al, 1998(Ochs et al, , 2001Birgersson and Karnland, 2009;.…”
Section: Introductionmentioning
confidence: 99%